Reputation and trust in health insurance: A scoping review of key drivers and outcomes - Gaël Saillen; Nicola Diviani; Sara Rubinelli (PLoS ONE, 2026)
Background Reputation is a critical factor in the health insurance industry, impacting business performance and public health outcomes. However, despite its acknowledged importance, the reputation of health insurers has received limited attention in both academic research and industry practice. Gaining a comprehensive understanding of health insurers’ reputation could help insurers strategically manage their public image while providing policymakers with valuable insights to develop policies that improve health outcomes. Objective This study aims to identify the factors shaping the reputation of health insurers and to assess the broader impacts of reputation within the industry and the health care system. Design A scoping review was conducted to map the existing literature on the reputation of health insurers. Using the PRISMA-ScR framework, it identified key determinants and outcomes of health insurer reputation, clarified concepts of reputation and trust, and highlighted gaps in the current body of literature. Results A total of 3385 records were identified, of which 397 were fully screened for eligibility, resulting in the inclusion of 45 studies. The majority of the included studies conducted surveys (n = 40), while the minority employed qualitative interviews (n = 6) and focus group discussions (n = 7). The total number of participants involved in the included studies is 31’344. The analysis identified 23 descriptives themes, which were organised into two main analytical categories: determinants and outcomes. The determinants included 17 descriptive themes which have been further classified into three groups based on whether they pertain to policyholders, insurers or providers. The outcomes consist of six key descriptive themes. Conclusion This review provides a thorough analysis of research that have investigated different aspects of health insurance reputation and identify significant gaps in the literature. It maps key determinants of reputation – such as corporate culture, product structure, and service quality – that insurers can directly influence. Additionally, factors like the quality of healthcare providers and targeted communication efforts may also be linked to reputation. The analysis underscores the importance of reputation for core business activities (e.g., client acquisition and retention) and its role in preventive healthcare. Notably, there is a lack of research on the regulatory implications of insurers’ reputation, suggesting a need for further studies to enhance preventive strategies and integrate insurers into a broader public health framework.